Design and validation of formative research skill scale - Calderón Gutierrez , Luis Carlos (2024)
The development of formative research skills involves the implementation of activities aimed at scientific research, which is considered fundamental for the development of countries in the 21st century. Despite this importance, there is no instrument with sufficient psychometric evidence. Within this framework, the present study aimed to design and validate a scale to measure formative research skills in the context of graduate students. An instrumental study was carried out on 187 master's students, aged between 24 to 68 years (M = 36.21; SD = 9.13), belonging to the majors of University Teaching (43.8%), Educational Management (38%). ) and Evaluation and Accreditation of the Quality of Education (18.2%) of a Peruvian public university, to whom a 35-item scale was administered. The content validation carried out with Aiken's V included relevance and clarity of wording of the items, and showed a value of .991 for the entire instrument. On the other hand, the confirmatory factor analysis reported adequate goodness-of-fit indices (x2/df = 1.264, RMSEA = .038, SRMR = .079, GFI = .954, CFI = .985, TLI = .983). Finally, an excellent level of reliability was obtained (w = .93). The EDHIF showed validity and reliability to measure the level of development of formative research skills in graduate students. In this way, a useful instrument is presented to determine the progress of investigative skills and make improvements in training areas.